A CAD model of triple bandpass filter implemented with mushroom structure. Issue 4 (24th October 2013) - Awasthi, Seema; Biswas, Animesh; Jaleel Akhtar, Mohammed
ABSTRACT This article demonstrates the design of planar triple‐band filter using mushroom resonator for significant size reduction of the order 80%. Here, mushroom type resonator is used to realize a triple passband filter using the coupling matrix approach. The electric and magnetic couplings between the mushroom resonators are achieved by proper positioning of corner via which have been analyzed and presented. Finally, the frequency transformation has been applied to design a highly selective 12‐pole triple‐passband cascaded‐quartets filter. This symmetric triple‐band filter is operative at center frequencies 3.41/3.56/3.72 GHz with 100 MHz bandwidth of each band. It is observed that the measured results are in good agreement with the simulated results. A significant size reduction has been achieved while realizing triple‐passband filter, which is as small as 50 mm × 25 mm × 1.27 mm. © 2013 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:421–428, 2014.